Effects of strontium - erbium co-doping on the structural properties of hydroxyapatite: An Experimental and theoretical study. Issue 10 (July 2020) - Mahmood, Bahroz Kareem; Kaygili, Omer; Bulut, Niyazi; Dorozhkin, Sergey V.; Ates, Tankut; Koytepe, Suleyman; Gürses, Canbolat; Ercan, Filiz; Kebiroglu, Hanifi; Agid, Riyadh Saeed; İnce, Turan
Abstract: Five different samples of Sr-based Er-doped hydroxyapatites (HAps) in the dissimilar quantities like 0, 0.35, 0.70, 1.05 and 1.40 at% were produced via a wet chemical process. The prepared samples were investigated experimentally by powder X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive X-ray (EDX), Fourier transform infrared (FTIR) spectroscopy, differential thermal analysis (DTA), and in vitro biocompatibility tests. In addition, the density of states (DOS) and band structures were investigated theoretically. It was found that the presence of Er as a dopant affected the lattice parameters, while the EDX measurements confirmed that the presence of Er at various concentrations caused a Ca-deficiency because the addition of Er decreased the Calcium/Phosphorus molar ratio from 1.67 to 1.61. For all samples, the single-phase distribution of HAp was observed. The crystallinity percentage of the samples was found to be 89% or more according to two different methods. The calculations with respect to Scherrer and Williamson-Hall methods showed that the crystallite sizes of the samples were found to be in the ranges of 29–34 nm and 25-42 nm, respectively. DTA investigations revealed that all samples exhibited thermal stability in the temperature range of 25 °C - 1000 °C. No remarkable morphological alterations were observed. Furthermore, the theoretical studies confirmed that the band structures narrowed with an increase in Er concentration.